2002
DOI: 10.1177/026119290203000110
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up to the ECVAM Prevalidation Study on In Vitro Tests for Acute Skin Irritation

Abstract: The European Centre for the Validation of Alternative Methods (ECVAM) Skin Irritation Task Force was established in 1996, to review the status of the development and validation of alternative tests for skin irritation and corrosion, and to identify appropriate non-animal tests for predicting human skin irritation that were sufficiently well-developed to be prevalidated and validated by ECVAM. The EpiDerm™ method, based on a reconstituted human skin model, was proposed as being sufficiently well advanced to ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 20 publications
1
56
0
3
Order By: Relevance
“…In conclusion, skin capacitance imaging appears to be a reliable tool in the evaluation of the irritative potential of a surfactant solution in non‐exaggerated conditions of use. This method can be added to the list of many in vitro and in vivo predictive methods presently available for rating the potential irritancy of surfactants (4, 9, 10, 16–18, 41, 42). Searching for more sensitive methods remains one of the goals in this field of research.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, skin capacitance imaging appears to be a reliable tool in the evaluation of the irritative potential of a surfactant solution in non‐exaggerated conditions of use. This method can be added to the list of many in vitro and in vivo predictive methods presently available for rating the potential irritancy of surfactants (4, 9, 10, 16–18, 41, 42). Searching for more sensitive methods remains one of the goals in this field of research.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically noted was the detection of irritation before visual evidence by evaporimetry in vivo (Zuang et al 2000). The main non-invasive test carried over for evaluation in vitro has been evaporimetry (Heylings et al 2001;Zuang et al 2002).…”
Section: History Of Alternative Methodsmentioning
confidence: 99%
“…Skin Model methods were conducted under the auspices of ECVAM (Fentem et al, 2001;Faller et al, 2002;Cotovio et al, 2005;Zuang et al, 2002). It was concluded that the modified in vitro EpiDerm TM ‚ Skin Irritation Test (EPI-200-SIT) showed evidence of being a reliable and relevant stand-alone replacement test for in vivo skin irritation testing (EURL-ECVAM, 2008) or a partial replacement test with a testing strategy (OECD, 2014).…”
Section: In Vitro Skin Irritation Test Of Honeypolis Using Humanmentioning
confidence: 99%